2005
DOI: 10.1097/01.inf.0000164705.74498.86
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Canadian Study of Hepatitis A Antibody Prevalence Among Children Eight to Thirteen Years Old

Abstract: The risk for hepatitis A during childhood is low in Canada. Almost all teenagers (>97%) would be at risk for infection in case of contact with HAV. Changes in immunization policy against hepatitis A should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 20 publications
(18 reference statements)
1
23
1
Order By: Relevance
“…There was no association between seropositivity and gender based on 9 population comparisons from 5 studies (n = 4158, URR: 1.0 [95% CI: 0.9, 1.1]) [22,31,35,41,54], which was consistent with results of 3 other studies reporting adjusted risk estimates (Table 3) [25,34,48]. Two studies in the early 1980's suggested that individuals living in urban areas were 30% more likely to have HAV antibody compared to those in rural areas (n = 647, URR: 1.3 [1.2, 1.5]) [41,46].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…There was no association between seropositivity and gender based on 9 population comparisons from 5 studies (n = 4158, URR: 1.0 [95% CI: 0.9, 1.1]) [22,31,35,41,54], which was consistent with results of 3 other studies reporting adjusted risk estimates (Table 3) [25,34,48]. Two studies in the early 1980's suggested that individuals living in urban areas were 30% more likely to have HAV antibody compared to those in rural areas (n = 647, URR: 1.3 [1.2, 1.5]) [41,46].…”
Section: Resultssupporting
confidence: 75%
“…The seroprevalence in Canadian-born children aged 8–13 was 1% [95% CI: 0.5–2%] according to a national survey conducted in 2003 [48]. The seroprevalence was 1–6% in ages 20–24, approximately 10% in 25–29, 17% in 30–39, and increased subsequently (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…[20,22,23] This factor was, however, significantly associated with anti-HAV antibody among Canadian children. [18] In this study, there appeared to be no influence of educational status on the anti-HAV antibody prevalence, as all the subgroups relating to this factor had high group-specific prevalence; the reason for this might be due to high endemicity of Nigeria for HAV infection and the prevailing unsanitary condition of Osogbo; the latter factor was once documented by Siegl. [3] Ramezani et al, [23] however, reported significantly lower anti-HAV prevalence rate among those with a high school or vocational level of education compared to those with a lower level of education.…”
Section: Discussionmentioning
confidence: 81%
“…[16] Separate studies of the rural population of southeastern Bolivia and Bangladeshi people, though with lower prevalence rates compare to our observation, also reported high anti-HAV antibody prevalence. [8,17] In Canada, Duval et al [18] observed anti-HAV IgG antibody prevalence of 2.7% (n ¼ 1,057) among 8-13 year old children. However, in this study, though the sample size in the 15 year old group was just two, 100% prevalence was observed (Table 1).…”
Section: Discussionmentioning
confidence: 98%
“…Most seroepidemiologic studies in Canada have been supported by time-limited research funds. 29,38,39,56,57 These studies show the epidemiologic and laboratory capacity to complete such work in Canada. Preliminary establishment of a network is likely to be started on a smaller scale in a limited number of participating provinces and territories, supported by research funds.…”
Section: Challenges To Implementationmentioning
confidence: 99%